The Inventory and Use of Suspected Cultural Heritage Objects (SCHO) in Bandar Lampung as Supplementary History Teaching Materials Based on Local Wisdom at YP UNILA Senior High School, Bandar Lampung - Maskun; Sumargono; Agus Mastrianto; Bahtiar Afwan; Navil Alfarisi Abbas (The Future of Education Journal, 2025)
This study aims to inventory and utilize the Suspected Cultural Heritage Objects (ODCB) in Bandar Lampung as supplementary teaching materials for local wisdom-based history lessons at SMA YP UNILA. The background of this research is based on the lack of attention to the preservation of local historical artifacts and the limited availability of teaching materials that are relevant to local wisdom. The research method used is descriptive qualitative with an approach that includes literature study, documentation, observation, and interviews to obtain in-depth data regarding the ODCB in Bandar Lampung. The results of the study indicate that ODCBs, such as bunkers and caves from the Japanese occupation, have great potential as interactive and relevant local history teaching materials. The implementation of ODCBs in learning has increased students' awareness of the importance of preserving local history. In conclusion, integrating ODCBs into history teaching materials can be an effective solution to enrich learning content and encourage student involvement in understanding historical values.